2018
DOI: 10.5534/wjmh.180042
|View full text |Cite
|
Sign up to set email alerts
|

Postmicturition Dribble Is Associated with Erectile Dysfunction in Middle-Aged and Older Men with Lower Urinary Tract Symptoms

Abstract: PurposeLower urinary tract symptoms (LUTS) are correlated with erectile dysfunction (ED), but research on whether postmicturition dribble (PMD) is related to ED is limited. We assessed the correlation between PMD and ED in middle-aged and older Korean men with LUTS.Materials and MethodsIn our prospective, cross-sectional, observational, multicenter study, we enrolled 205 men (age >40 years) with LUTS. LUTS and ED were assessed using the International Prostate Symptom Score (IPSS) and International Index of Ere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 28 publications
0
19
0
3
Order By: Relevance
“…It is possible to divide LUTS into storage, voiding and postmicturition symptoms [1]; however, almost all LUTS treatments are focused on storage and voiding symptoms, not on post-micturition symptoms [1,2], and even LUTS research does not focus on post-micturition symptoms. Physicians' and researchers' indifference to post-micturition symptoms may be attributable to the traditional belief that post-micturition symptoms may be a part of the aging process, have a low prevalence, and elicit less discomfort than other LUTS [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible to divide LUTS into storage, voiding and postmicturition symptoms [1]; however, almost all LUTS treatments are focused on storage and voiding symptoms, not on post-micturition symptoms [1,2], and even LUTS research does not focus on post-micturition symptoms. Physicians' and researchers' indifference to post-micturition symptoms may be attributable to the traditional belief that post-micturition symptoms may be a part of the aging process, have a low prevalence, and elicit less discomfort than other LUTS [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Several epidemiological studies report that there may be a close association between PMD and erectile dysfunction (ED) . Recent experimental studies have also shown that corpus cavernosum structural changes may be related to the post‐micturition residual urine volume in the bulbous urethra .…”
Section: Introductionmentioning
confidence: 99%
“…Consultation on Incontinence-Short Form (ICIQ-SF) é uma ferramenta de grau a muito utilizada para avaliação da incontinência urinária possui uma questão que não se pontua no escore total do instrumento estando relacionada ao tipo de perda urinária e cujas alternativas de resposta incluem a perda por GPM (27) (28)(29)(30).…”
Section: Criado Para Superar Algumas Limitações Do Ipss O Internationunclassified
“…Encontramos em nossa pesquisa a disfunção erétil e a ejaculação precoce como preditores para o GPM. Um estudo envolvendo homens coreanos meia idade com sintomas urinários diagnosticados através do IPSS e HPMDQ e a disfunção erétil avaliada pelo IIEF-5 observaram a correlação entre disfunção erétil e GPM (29). Os autores concluíram que o GPM poderia ter um papel importante na associação entre sintomas urinários e disfunção erétil e a prevalência da desta última, estava estatisticamente relacionada com a gravidade do GPM (29).…”
Section: Epidemiologia Do Gpm Na Amostra Da Populaçãounclassified
See 1 more Smart Citation